(untitled) (International Journal of Engineering and Computer Science, 2018)
Message authentication is one of the most efficient way to keep the data safe from unauthorized access and corrupted messages which is being forwarded in wireless sensor networks (WSNs). For this reason, many message authentication schemes have been developed, based on either symmetric-key cryptosystems or public-key cryptosystems. Many schemes have the restrictions of high computational and communication transparency and deficient in the scalability to node compromise attacks. To address these issues, a polynomial-based scheme was recently introduced. However, this scheme and its extensions all have the weakness of higher processing time determined by the degree of the polynomial when the number of messages transmitted is larger, the adversary can fully recover the polynomial. This system allows the intermediate nodes authentication to transmit a larger number of messages without suffering with the time complexity problem. It is basically design to authenticate the message in network while transferring. Here we will utilize the elliptic curve polynomial y2 = (x3 + ax + b) mod p and comparison will be done between transmission with and without security mechanism of signatures. To prove that our approach is better than Polynomial based scheme we compare result between Elgamal signature analyses with ECC polynomial signature analysis.